2005
DOI: 10.1113/jphysiol.2005.093526
|View full text |Cite
|
Sign up to set email alerts
|

Water permeability of Na+–K+–2Cl cotransporters in mammalian epithelial cells

Abstract: Water transport properties of the Na + -K + -2Cl − cotransporter (NKCC) were studied in cultures of pigmented epithelial cells (PE) from the ciliary body of the eye. Here, the membrane that faces upwards contains NKCCs and can be subjected to rapid changes in bathing solution composition and osmolarity. The anatomy of the cultured cell layer was investigated by light and electron microscopy. The transport rate of the cotransporter was determined from the bumetanide-sensitive component of 86 Rb + uptake, and vo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
49
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 65 publications
(57 citation statements)
references
References 26 publications
7
49
1
Order By: Relevance
“…We have previously demonstrated a temporal profile of changes in AQP4 expression following experimental stroke [43]. Our study cannot rule out the direct possible effect of bumetanide on inhibiting water transport through Na + -K + -2Cl -cotransporter itself or other cotransporters as demonstrated by previous studies [44,45].…”
Section: Discussioncontrasting
confidence: 59%
“…We have previously demonstrated a temporal profile of changes in AQP4 expression following experimental stroke [43]. Our study cannot rule out the direct possible effect of bumetanide on inhibiting water transport through Na + -K + -2Cl -cotransporter itself or other cotransporters as demonstrated by previous studies [44,45].…”
Section: Discussioncontrasting
confidence: 59%
“…Reports of membrane permeability values that appear to decrease with increasing osmolality are not uncommon in the published literature. 1,8,9,28,34,37 Whereas the authors of such studies have attributed the observed trends to some property of the cell membrane that changes with osmolality or with direction of water flow, a more likely explanation may be that the apparent dependence of L p on P e is caused by artifacts due to solute transport limitations in the extracellular solution.…”
Section: Discussionmentioning
confidence: 86%
“…Although a similar strategy has previously been proposed by Farinas et al, 6 this approach is seldom utilized in the literature. For example, both Maran˜on et al 21 and Hamann et al 9 have reported that slow solution exchange kinetics limited the accuracy of their membrane permeability estimates, but both groups measured the transient cell volume change only after exposure to hypertonic solutions; had reduction of the perfusate osmolality been attempted in these studies, the accuracy of the permeability estimates may have improved. Despite the evident benefits of reducing perfusate osmolality, this strategy has some limitations.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations